LABORATORY WASTEWATER TREATMENT USING MICROBIAL FUEL CELL: A FUTURE PARADIGM OF SUSTAINABILITY - Turin Afroz (Faculty of Vocational Studies, Universitas Airlangga, 2025)
Background: In Southwestern Bangladesh, the absence of safe drinking water is a severe catastrophe. Coastal inhabitants were pressured to drink saline water and were not able to fetch conveyable drinking water. The Incremental Lifetime Cancer Risk value for Cr, Ni, Cd of mine area of Dinajpur, Hazaribagh tannery, Singair, Manikgonj, Rajshahi city and Chuadanga is found from 18.2 × 10−3 to 1.32 × 10−3 where more than 1 × 10–4 is considered significant. At present the global burden of excreta-related syndrome is enormously high. Therefore, laboratory wastewater treatment is an urgent need. Purpose: A microbial fuel cell can be considered a sustainable tool to mitigate this problem. The findings of this study will help the reader to know that biotechnology in the laboratory is a self-sustaining wastewater treatment method. Future direction is also anticipated. Moreover, people will be able to understand the wise use of water. Review: It was a descriptive type of qualitative study with a literature review. The literature research was performed electronically through Springer, PubMed, Google Scholar and distinctive databases. The literature published between 2013 - 2024 was searched to identify the relevant literature using the keywords: “Microbial fuel cells,” “sustainability,” “wastewater,” “saline water,” and “Bangladesh.” Result: This study explored different studies related to the existing mechanism of MFC in wastewater treatment. The paper highlighted remarkable research from 2016 to 2024 as well as challenges and solutions to these challenges in scaling up MFC. Conclusion: The author strongly recommends that laboratory wastewater treatment by microbial fuel cells is a paradigm of sustainability for its capability of low sludge production results in a reduction of secondary pollution and low carbon footprint arising from less fossil-related CO2 production as a result of low energy consumption. A lot more work is essential in the field to produce a sustainable energy source in countries like Bangladesh.